Worker representation and temporary employment in Germany: The deployment and extent of fixed-term contracts and temporary agency work - Addison, John T.; Teixeira, Paulino; Grunau, Philipp; Bellmann, Lutz (Journal of Participation and Employee Ownership, 2019)
Purpose: The purpose of this paper is to investigate the impact of key labor institutions on the occurrence and extent of temporary employment. Design/methodology/approach: In a new departure, this study uses a zero-inflated negative binomial (ZINB) model given that most establishments are non-users of either fixed-term contracts (FTCs) or temporary agency workers. Findings: This study examines the potential impact of works councils and unions on the use and intensity of use of FTCs and temporary agency work. There is a little indication that these variables are correlated with the use/non-use of either type of temporary work, especially in the case of FTCs. Collective bargaining displays different relationships with their intensity of use: a negative association for sectoral bargaining and FTCs and the converse for firm-level bargaining and agency temps. Of more interest, however, is the covariation between the number of temporary employees and the interaction between works councils and product market volatility. The intensity of use of agency temps (FTCs) is predicted to rise (fall) as volatility increases whenever a works council is present. These disparities require further investigation but most likely reflect differences in function, with agency work being more directed toward the protection of an arguably shrinking core and fixed-term contacts encountering resistance to their increased use as a buffer stock. The two types of temporary employment are seemingly non-complementary, an interpretation that receives support from the study’s further analysis of FTC flow data. Research limitations/implications: The non-complementarity of the two types of contract is the hallmark of this paper. Originality/value: The first study to deploy a ZINB model to examine both the occurrence and incidence of temporary work.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Complementarity; Demand volatility; Germany; Temporary employment; Worker representation; Zero-inflated negative binomial model